Gestantes de alto risco em programa de alta hospitalar qualificada: personalidade, estilo de vida e vivências - Porto, Mariana Alves (2018)
The Program of Qualified Hospital Discharge, composed by a multidisciplinary team, aims to evaluate and identify the social, physical and psychological needs of pregnant women those are high risk and are hospitalized, in order to these women would contact the Health Care Network in the moment of their hospital discharge, to prevent new complications with the patients under discussion. The goal of this present study was outline the sociodemographic profile, lifestyle and personality, as well as, to understand the experiences of women included in this program. Data collection involved the surveys: sociodemographic, “Fantastic” Lifestyle, Personal Beliefs (PBQ – SF) and comprehensive interview. The quantitative data were submitted to descriptive analysis, while the qualitative data were analyzed in the phenomenological modality. The sample included 13 hospitalized risk pregnant women, with average age of 24 years. Among them, mostly are in stable union, completed high school, have a religious belief and declare themselves as housewives. The multiparity is present in 61.5% (N=8) and 61.5% did not have an abortion history before. The majority showed a good lifestyle and the personality profiles those are more common are: schizoid, avoidant and dependent. In relation to the experiences, five categories emerged: Fear, Concern, Faith as a confrontation appeal, importance of the social support and professional-patient relationship. The study is relevant, since the demand comprehension of the assisted population provides subsidies to the assistance adjustment and the elaboration of a more reliable therapeutic plan.